A proposal of Android Programming Learning Assistant System with implementation of basic application learning. Issue 1 (3rd October 2019) - Syaifudin, Yan Watequlis; Funabiki, Nobuo; Kuribayashi, Minoru; Kao, Wen-Chung
Abstract : Purpose: With rapid increase of Android devices and application systems, there is a strong demand for Android application programmers. A lot of schools are offering Android programming courses to meet this demand. However, Android programming can be different from the conventional one because it needs interactive functions through interfaces with users, which makes the study more difficult. This paper aims to propose an Android Programming Learning Assistance System, namely, APLAS, to assist the Java-based Android programming study and education. Design/methodology/approach: By adopting the test-driven development method, APLAS is designed to achieve independent learning without the presence of teachers. Using JUnit and Robolectric, the answers from the students are automatically marked in APLAS. To cover extensive materials in Android programming, APLAS offers four stages where each stage involves several topics. Findings: To evaluate the effectiveness of APLAS, we implemented the Unit Converter assignment that covers the first two topics, namely, Basic user interface in the first stage and basic activity in the second stage. Through solving the assignment, it is expected to learn basic application development. Forty novice students of an IT department in Indonesia were asked to solve both topics separately. Originality/value: The results show that APLAS is useful and helpful for the self-study of Android programming, as they could complete codes with good execution performances.